Point-of-care testing of hyponatremia and hypernatremia levels: An optoplasmonic biosensing approach. - Abdullah Mohammad Tanvirul Hoque; Abrar Islam; Firoz Haider; Rifat Ahmmed Aoni; Rajib Ahmed (PLoS ONE)
In the human body, sodium ion (Na+) is the principal extracellular cation and its imbalance in blood or lymph results in either hyponatremia or hypernatremia conditions. Any of these scenarios have fatal effects on a patient's health over time. However, the existing technologies limit quick point-of-care (POC) testing options. To overcome the challenges associated with prompt diagnosis, we proposed a photonic crystal fiber (PCF) based surface plasmon resonance (SPR) sensor for in situ rapid testing of Na+ ion levels in patient's blood samples. A unique PCF sensor with a modified square lattice is engineered to achieve a propagation-controlled core that permits enhanced control over wave guidance resulting in improved sensing performance. Plasmonically active conducting indium tin oxide (ITO) is used to omit the limitations that arise from undesired oxidation with time and to enable higher spectral tunability. The finite element method (FEM) is used to perform the numerical analysis on performance and all sensor parameters are optimized to ensure the best sensing outcome. The structural asymmetry-induced birefringence enforced a superior y-polarized sensing response compared to that of the x-polarized mode for the proposed sensor, where it proffers the highest wavelength sensitivity of 15,157 nm/RIU with a detection resolution of 6.61 ×  10-6 RIU. Additionally, the sensor exhibits a maximum amplitude sensitivity of 470 RIU-1 and an outstanding figure of merit (FOM) of 171 RIU-1. Due to the high sensitivity and resolution, we infer that the proposed sensor will be a promising POC alternative to the conventional serum electrolyte panels used in present medical practice.